2023
DOI: 10.1101/2023.03.06.531398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zebrahub – Multimodal Zebrafish Developmental Atlas Reveals the State-Transition Dynamics of Late-Vertebrate Pluripotent Axial Progenitors

Abstract: Elucidating the developmental process of an organism will require the complete cartography of cellular lineages in the spatial, temporal, and molecular domains. We present Zebrahub, a comprehensive dynamic atlas of zebrafish embryonic development that combines single-cell sequencing time course data with light-sheet microscopy-based lineage reconstructions. Zebrahub is a foundational resource to study developmental processes at both transcriptional and spatiotemporal levels. It is publicly accessible as a web-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 76 publications
2
50
0
Order By: Relevance
“…S2B). Interestingly, single-cell RNA-Seq datasets revealed that TLNRD1 expression peaks at 24 h post-fertilization during zebrafish embryo development, where it is principally expressed in the blood vasculature (Zebrahub (Lange et al, 2023)). Similarly, TL-NRD1 is also expressed in the vasculature in human embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2B). Interestingly, single-cell RNA-Seq datasets revealed that TLNRD1 expression peaks at 24 h post-fertilization during zebrafish embryo development, where it is principally expressed in the blood vasculature (Zebrahub (Lange et al, 2023)). Similarly, TL-NRD1 is also expressed in the vasculature in human embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to further explore the tissue specificity of expression of DEGs at 24 hpf. To this end, we used existing single-cell RNA-seq dataset produced by the Zebrahub partners (Lange et al, 2023) to which we applied a dimensionality reduction approach (Marquez-Galera et al, 2022) to differentiate between cell-type-specific signals in bulk RNA-seq DEGs according to the single-cell RNA-seq data at 24 hpf. This approach allows us to increase the accuracy of the spatial distribution of the DEGs as well as the specificity to developmental stages F I G U R E 4 Paternal starvation does not alter F2 survival but is associated with F2 malformations at 24 hpf.…”
Section: Impact Of Paternal Diet On the F1 Transcriptomementioning
confidence: 99%
“…These atlases are now instrumental for studying a wide range of tissues, organs, and even whole organisms to reveal the origins of cellular differentiation and functional diversity [Quake 2022, Tabula Sapiens Consortium 2022]. Further combined with spatial and time-series studies, they offer a high-definition window into biological development over space and time [Calderon 2022, Qiu 2023, Packer 2019, Sala 2019, Lange 2023]. However, the growing scale of single-cell atlases often poses daunting analytical challenges [Sikkema 2023, Qiu 2023, Lange 2023].…”
Section: Introductionmentioning
confidence: 99%